Dengar Pendapat Publik (Public Hearing) tentang Rancangan Qanun Pengelolaan Barang Milik Daerah Kabupaten Aceh Utara - Yulia, Yulia; jamaluddin, Jamaluddin; Yusrizal, Yusrizal (Jurnal Malikussaleh Mengabdi, 2025)
Public hearing Draft Regional Property Management Qanun is a participatory forum involving various stakeholders to provide input on regulations governing regional government assets. This activity aims to ensure that the qanun prepared can accommodate the principles of transparency, accountability and efficiency in the management of regional property, in accordance with applicable laws and regulations. The method of implementing the activity is through questions and answers and discussions between the Baleng DPRK Team, the Drafting Team and the Participants. In this public discussion, various aspects are discussed, including mechanisms for planning, procurement, utilization, maintenance, supervision and disposal of regional assets. The participation of the community, academics, representatives of government and private institutions is a key factor in preparing a Draft Qanun that is responsive to the needs of North Aceh Regency. The results of public hearings can be the basis for improving the Draft Qanun before it is ratified, so that it can support more efficient and sustainable management of regional property.